Growth and Development of Soybean Plants with the Pat Gene under different Glufosinate Rates - Mundt, Tamara Thaís [UNESP]; Albrecht, Leandro Paiola; Albrecht, Alfredo Junior Paiola; Krenchinski, Fábio Henrique [UNESP]; Pereira, Vinícius Gabriel Caneppele [UNESP]; Wagner, Felipe Gustavo; Silva, André Felipe Moreira; Carbonari, Caio Antonio [UNESP] (Friends Science Publishers, 2021)
The pat gene confers tolerance to glufosinate in transgenic soybean plants; however, some aspects of the selectivity of this herbicide need to be better elucidated. This study aimed to evaluate the development of soybean plants with the pat gene under the application of different glufosinate rates. The experiment was conducted in a greenhouse and included seven different glufosinate rates of and two soybean cultivars (LL0291 and LL0767) with the pat gene, with four replications in a completely randomized design. Glufosinate was applied at the V4 stage (4 nodes on the main stem with fully developed leaves beginning with the unifoliolate nodes) of soybean, and the variables analyzed were: soybean injury, chlorophyll index, plant height, dry and fresh matter of shoots and roots, wet nodules, dry nodules, and total number of nodules. It was found that for both cultivars, the maximum recommended glufosinate rate of 700 g of active ingredient (ai) ha-1 was safe, rates above 1,250 g ai ha-1 may interfere with development, especially biomass accumulation, and, in general, cultivar LL0291 exhibited more injuries than cultivar LL0767. The glufosinate-tolerant soybean (with pat gene) is a great option for farmers, but care should be taken with respect to rates above the maximum recommended in the package insert, so that there is no damage to soybean.
Keywords: Chlorophyll indices; Crop injury; Glycine max L.; Liberty link®; Selectivity